PENGENDALIAN HIPERTENSI MELALUI PEMBERIAN EDUKASI GIAT (GAYA HIDUP SEHAT) SEBAGAI UPAYA PENINGKATAN PENGETAHUAN PENDERITA HIPERTENSI - DERI RAMADHAN, MUHAMMAD (Jurnal LENTERA, 2025)
The incidence of hypertension continues to increase annually, thus requiring special attention needed from all parties, especially patients and health care professionals. The key to the success of a therapy regimen among patients with hypertension is a change in healthy lifestyle through good self-care skills and compliance in taking antihypertensive medication as an effort to control hypertension. If hypertension is not controlled properly, it can cause various complications. A cognitive approach is one of the best ways to increase literacy about hypertension through providing health education. The aim of program was to improve knowledge about hypertension controlling among patients with hypertension. The method used is health education about a healthy lifestyle among patients with hypertension for 120 minutes, consisting of three stages including preparation, implementation, evaluation and follow-up. The results of this activity obtained information that there was an increase in knowledge among patients with hypertension, with an average score before and after providing education (56,49 and 77,48). The conclusion of the educational activity is proven to increase the knowledge of hypertension sufferers. This activity is recommended to be carried out routinely to